Pesquisas contemporâneas em religião = Contemporary research in religion - Tadvald, Marcelo (Ciencias sociales y religión, 2018)
On the eve of completing 20 years of activity, the journal Social Sciences and Religion / Ciencias Sociales y Religión (CS & rR), continues to give voice to investigations on religious phenomena since Latin America. In this sense, in this issue we bring together texts that examine the most different religious issues that are currently presented, through ethnographic, sociological, political, historical and other approaches, or even an arrangement between them, which show how varied contemporary research is. and the ways in which the religious can manifest himself, in a unique, exclusive, plural and multilocalized way.